Analysis of Grammatical Cohesion in Qira’at Text (The Reading) of Al-Arabiya Baina Yadaik Ii Book - Mohammad Ahsanuddin; Ali Ma'sum (Dinamika Ilmu, 2021)
This study aims to describe referential devices, substitution ellipsis, and conjunction in qira’at (the reading) text of Al-Arabiya Baina Yadaik (ABY) II book. This research uses a qualitative method in an appropriate setting with a grammatical cohesion analysis approach to identify the grammatical elements from a reference perspective within the qira’at text in the ABY II book. The obtained data subsists of grammatical cohesion, including referential devices, substitution, ellipsis, and conjunction in qira’at (the reading) text. Due to the limited research time, there were only eight qira’at texts, from wihdah (unit) 1-8 of the ABY II book, explored in this research. The results indicate that (1) the referential devices in the qira’at texts is personal (subsisting of third-person singular ‘mufrad’, dual ‘mutsanna’, and plural), demonstrative ( the word ذلك) and comparative (the words that compare sentences); (2) the identified substitution devices are nominal and clause substitution; (3) the discovered ellipsis devices are nominal, verbal and clause ellipsis; and (4) the found conjunction devices are temporal, causal, additive, and adversative.